Interdiciplinary between heritage and creative? - Iwan Zahar (2011)
Interdiciplinary between two different courses or more will be important for student in the future. FTKW (Faculty of Creative Technology and Heritage), UMK, is an art faculty in Malaysia which integrates art, heritage, and bussiness. FTKW UMK starts to implement interdiciplinary since the first three semester. This novel idea is to make learning reflects real-world experience more accurately. Today, most contemporary jobs require integration of a range skills; therefore, heritage and creative students learn various subject matter including painting, computer, enterpreneuship, Melayu cultures, visual representation, and traditional craft in their first three semester. However, most students do not automatically can integrate various subject matter by them selves. We need to developed interdicipline curriculums. This paper recommend interdicipline method to integrate the different dicipline.